Perceived Value terhadap Repurchase Intention yang Dimediasi Customer Trust pada E-Commerce Tokopedia di Kota Bandung - Refanda Putri Cahyaningtiyas; Eka Ludiya (Journal of Management and Bussines (JOMB), 2024)
This research aims to explore the influence of perceived value on repurchase intention mediated by customer trust on the Tokopedia e-commerce platform in Bandung City. The data collection method used was a survey using an online questionnaire. The research results have gone through the stages of validity and reliability testing, classical assumption testing, simple regression testing, multiple regression and Sobel testing. SPSS version 25 software tools and an online Sobel calculator were used to analyze the data. The research results show that the four hypotheses successfully reject H0, which means that perceived value has a positive and significant effect on repurchase intention which is mediated by customer trust. In conclusion, this research provides a deeper understanding of the relationship between perceived value, customer trust, and repurchase intention in the context of e-commerce. Keywords: Customer Trust, Perceived Value, Repurchase Intention